Finite-State Morphology Code With Compiled Analyzers And Generators For Skolt Sami - Rueter, Jack Michael (Zenodo, 2018)
Two-level morphophonology and lexc morphological descriptions of Skolt Sami as coded on the Giella Infrastructure at the Arctic University of Norway, in Tromsø. Funded by scholarship from Kone Foundation